2017
DOI: 10.1021/acs.energyfuels.7b03071
|View full text |Cite
|
Sign up to set email alerts
|

A pH-Resolved Wettability Alteration: Implications for CO2-Assisted EOR in Carbonate Reservoirs

Abstract: Wettability of an oil/brine/rock system is a critical petrophysical parameter, which governs subsurface multiphase flow behavior, thus hydrocarbon recovery. While the mechanisms of CO2-assisted enhanced oil recovery (EOR) techniques have been extensively investigated in carbonate reservoirs, few have been done to identify the controlling factor of CO2-induced wettability alteration, and fewer have looked beyond the implications for CO2-assisted EOR. We thus hypothesize that CO2-assisted EOR techniques cause a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 37 publications
1
19
0
2
Order By: Relevance
“…This is because non-carbonated brine gives a strongly negative surface potential, whereas the surface potential of brine-calcite remains positive, triggering attractive forces. We believe that both electrostatic and nonelectrostatic physisorption together with competitive ion chemisorption (ion exchange and surface complexation modelling) 38 would be combined to better account for the total disjoining pressure.
Figure 9 Total disjoing pressure under the condition of constant charge (solid lines) and constant potential (dotted lines) versus film thickness in the presence of carbonated and non-carbonated brines with different ion type and salinity.
…”
Section: Resultsmentioning
confidence: 99%
“…This is because non-carbonated brine gives a strongly negative surface potential, whereas the surface potential of brine-calcite remains positive, triggering attractive forces. We believe that both electrostatic and nonelectrostatic physisorption together with competitive ion chemisorption (ion exchange and surface complexation modelling) 38 would be combined to better account for the total disjoining pressure.
Figure 9 Total disjoing pressure under the condition of constant charge (solid lines) and constant potential (dotted lines) versus film thickness in the presence of carbonated and non-carbonated brines with different ion type and salinity.
…”
Section: Resultsmentioning
confidence: 99%
“…While wettability alternation is considered as the main mechanism behind LSE, the understanding of which factors control the wettability variation is incomplete due to the complexity of the interactions occurring in the oil/brine/rock system. The two approaches that reveal the controlling factors behind the wettability alteration are (a) double-layer expansion between fine particles and limited fines release (LFR) between oil/rock contact areas (Nasralla and Nasr-El-Din 2014;Tang and Morrow 1999a;Xie et al 2016) and (b) surface complexation modeling (Brady and Krumhansl 2012;Brady and Thyne 2016;Brady et al 2015;Mahani et al 2017;Xie et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is mostly because elevating the pH of the brine causes deprotonation of the carboxylic functional group according to the reaction R−COOH = R−COO − + H + , which is well supported by published literature. 38,41,81 For instance, Brady et al 81 conducted geochemical modeling to investigate the impact of pH variation on the oil surface species. They found that raising the pH of sodium chloride brine from 4 to 9 causes an increase in the density of −COO − in the oil surface from 4 to 6 μmol/m 2 , suggesting that at high pH values the oil surface charge would be predominated by the −COO − oil group.…”
Section: ■ Experimental Methodologymentioning
confidence: 99%